1999
DOI: 10.1038/sj.onc.1202782
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and relocation of the tyrosine kinase P59FYN during Fas-mediated apoptosis in T lymphocytes

Abstract: Ligation of Fas with its natural ligand or with anti-Fas antibodies induces an apoptotic program in Fas sensitive cells. We report here the identi®cation of the tyrosine kinase p59Fyn as a substrate for CPP32-like proteinases and more particularly caspase 3 during Fas-mediated apoptosis in Jurkat T cells. Inhibition of CPP32-like proteinases by Ac-Asp-Glu-Val-Asp-aldehyde but not by Ac-Tyr-Val-Ala-Asp-aldehyde prevents CPP32, PARP and p59Fyn cleavage indicating that CPP32 or CPP32-like proteinases are responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Interestingly, the main cleavage site in Mcl-1, that is, EELD/G is closely related to the cleavage sites EEED/ G, EERD/G, EEAD/A and EETD/L previously identified in Topoisomerase-1, p59-Fyn, Caspase-2 and SRF, respectively (Li et al, 1997;Earnshaw et al, 1999;Ricci et al, 1999;Bertolotto et al, 2000;Luciano et al, 2001). More interestingly the EELD/G site in Mcl-1 is remarkably conserved in several mammal species whereas it does exist as a significant variation in the second Mcl-1 caspase site (TSTD/G in the human protein), reinforcing the notion that EELD/G represents the physiological caspase cleavage site of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the main cleavage site in Mcl-1, that is, EELD/G is closely related to the cleavage sites EEED/ G, EERD/G, EEAD/A and EETD/L previously identified in Topoisomerase-1, p59-Fyn, Caspase-2 and SRF, respectively (Li et al, 1997;Earnshaw et al, 1999;Ricci et al, 1999;Bertolotto et al, 2000;Luciano et al, 2001). More interestingly the EELD/G site in Mcl-1 is remarkably conserved in several mammal species whereas it does exist as a significant variation in the second Mcl-1 caspase site (TSTD/G in the human protein), reinforcing the notion that EELD/G represents the physiological caspase cleavage site of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, both cell lines were found to express p59 Hck, a Src kinase whose distribution is supposed to be largely restricted to myelomonocytic cell lines (Willman et al, 1991). We and others have previously reported that both cell lines were sensitive to Fas-killing (Ricci et al, 1999;Scadi et al, 1998). Induction of apoptosis by the agonistic anti-Fas mAb (CH11) was monitored as a function of time by the cleavage of procaspase 3 (Figure 1a).…”
Section: Cleavage Of Fyn and Lyn In Fas-stimulated T And B Cell Linesmentioning
confidence: 99%
“…We have previously shown that p59 Fyn is cleaved in Jurkat T-cells undergoing apoptosis (Ricci et al, 1999). To determine whether other Src kinases present in hematopoietic cell lines could be substrate for caspases, we looked for Fyn, Lyn, Lck and Hck processing in two cellular models that expressed or not these dierent kinases.…”
Section: Cleavage Of Fyn and Lyn In Fas-stimulated T And B Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Src-like tyrosine kinase, p56Lck, has been reported to mediate activation of an outwardly rectifying Cl Ϫ channel in lymphocytes stimulated with Fas ligand (5). Caspase is known to be activated by ROS (29,30) and to cleave p56Lck at the N-terminal domain (31,32). However, it is well known that AVD occurs upstream of caspase activation (7,(33)(34)(35).…”
Section: Conclusion and Perspectivementioning
confidence: 99%